Revisiting the interaction of highly nonlinear solitary wave with wall: From infinite to finite thickness. (1st April 2022) - Peng, Qing; Liu, Xiaoming; Shi, Xinghua; Wei, YueGuang
Graphical abstract: Highlights: Universal control equations are derived for the reflection of an HNSW against a plate. Two force models connect the features of solitary wave to the material and thickness of plate. We propose a non-destructive evaluation method to identify thin-wall structure. Abstract: The classical reflection of a highly nonlinear solitary wave (HNSW) on an elastic wall has been used to determine the material properties of the wall, but does not work on a plate (a wall with finite thickness). In this paper, by coupling sphere-plate contact with chain dynamics, we revealed that: with the same initial velocity, the energy dissipation of multi-sphere plate impact is different from the single sphere plate impact, but the contact force on the plate performs similarly. Based on this fact, we then developed two universal force models considering the dissipative feature of the plate. These force models (reflection force on the chain and contact force on the plate) can universally connect the signals of the HNSW with the dissipative feature of the plate. With the obtained force models, we proposed a non-destructive evaluation method, which can identify both the plate material and thickness by measuring the two forces: the reflection force on the chain and the contact force on the plate. Agreement with finite element simulations suggests that non-destructive evaluation of thin-walled structure can be realized by using HNSW with the proposed method.